Analysis of different heat pumping technologies integrating small scale solid oxide fuel cell system for more efficient building heating systems. (9th November 2015) - Frazzica, A.; Briguglio, N.; Sapienza, A.; Freni, A.; Brunaccini, G.; Antonucci, V.; Ferraro, M.
Abstract: Development of advanced heating systems, able to reduce the energy consumption of buildings is still an open issue. Different technologies, either already at commercial level or in a pre-commercial phase, are available. Among them, heat pumps and fuel cells represent good options, thanks to their high efficiency and flexibility of operation. The present paper analyses one of the possible ways to integrate a heat pump with a micro-Combined Heat and Power (CHP) based on Solid Oxide Fuel Cell (SOFC) technology, in order to increase the overall efficiency of the building heating system. Three different heat pumping technologies (namely vapour compression, absorption and adsorption) have been employed. Starting from performance data of commercial appliances (vapour compression and absorption heat pumps) and from performance experimentally measured at the CNR ITAE for appliances at prototyping level (adsorption heat pump and SOFC), a numerical model has been developed in TRNSYS. Simulations performed demonstrated that the overall yearly efficiency can be improved up to 30%, exploiting the heat released by the micro CHP to reduce the heat produced by the heat pump. Highlights: SOFC CHP System integrated with different heat pump technologies. Experimental data and numerical model developed in TRNSYS environment. Efficient building heating system.